2021
DOI: 10.3390/biology10020071
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Genetic Diversity of Weedy Rice Associated with Ambient Temperatures and Limited Gene Flow

Abstract: Hypotheses regarding the association of increased species or genetic diversity with gradually warmer regions as a global pattern have been proposed, but no direct and solid experimental data are available to approve the association between plant genetic diversity and ambient temperatures. To test the diversity-temperature hypothesis, we studied genetic diversity and genetic differentiation of weedy rice (Oryza sativa f. spontanea) populations occurring naturally in early- and late-season rice fields that share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…Generally, phenological conditions, such as temperature and photoperiod, between the two seasons are considerably different. Noticeably, differential genetic diversity and considerable genetic differentiation between the early-and late-season WR populations had been reported by Kong et al [21]. Therefore, we believe that such considerable genetic differentiation is accompanied by an inevitable phenotypic divergence between the two-season WR populations in the same rice elds, probably caused by the adaptive evolution in the weedy rice populations.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Generally, phenological conditions, such as temperature and photoperiod, between the two seasons are considerably different. Noticeably, differential genetic diversity and considerable genetic differentiation between the early-and late-season WR populations had been reported by Kong et al [21]. Therefore, we believe that such considerable genetic differentiation is accompanied by an inevitable phenotypic divergence between the two-season WR populations in the same rice elds, probably caused by the adaptive evolution in the weedy rice populations.…”
Section: Introductionsupporting
confidence: 61%
“…Interestingly, the limited gene ow between the two-season weedy rice populations was also proposed by Kong et al [21], which was explained to maintain genetic diversity within populations. This nding provided evidence of two cryptical populations in the same rice eld and suggested that the weedy rice individuals, which adapted to low temperature and long day length conditions, can survive and only retain in the early rice-cultivation season.…”
Section: Phenotypic Differentiation Between the Sympatric Weedy Rice Populations Is Associated With Local Adaptationmentioning
confidence: 63%
See 1 more Smart Citation
“…As a conspecific taxon, WR evolves rapidly under the influence of its cultivated counterparts and human activities (Jiang et al ., 2012; Zhu et al ., 2021). In some tropical regions in the world, rice is grown for two seasons per year, namely the early and late seasons, when WR also co‐occurs in the two seasons' rice fields (Li et al ., 2013; Kong et al ., 2021). In southern China, rice production is characterised by intensive farming by small farmer households with a rapid shift from traditional seedling transplanting to direct seeding, in addition to less field management due to the lack of a labour force, which causes serious weed problems, including by WR.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences can serve as important sources for the divergent selection of plant taxa. A previous study indicated detectable increases in genetic diversity associated with the higher ambient temperature in the late‐season WR populations collected from Leizhou based on the selected microsatellite fingerprints (Kong et al ., 2021). Results obtained from that study suggested potential genetic divergence between the early‐ and late‐season populations of WR co‐occurring in the same rice fields.…”
Section: Introductionmentioning
confidence: 99%